Relationship between amikacin blood concentration and ototoxicity in low birth weight infants. Issue 1 (January 2019) - Endo, Aiju; Nemoto, Atsushi; Hanawa, Kazumi; Maebayashi, Yuki; Hasebe, Yohei; Kobayashi, Mami; Naito, Atsushi; Kobayashi, Yoshifumi; Yamamoto, Seiichi; Isobe, Katsuhiko
Abstract: Amikacin (AMK) is used as empiric therapy for severe infections such as sepsis in low birth weight (LBW) infants. AMK administered once daily (OD) in adults is reported to be therapeutically effective and prevent side effects, however, evidence on AMK administration in LBW infants is limited, with no clear indications of effectiveness. We performed therapeutic drug monitoring analysis of 20 infants treated with AMK OD for severe infections such as bacteremia. Treatment effectiveness was admitted by the patients' medical records, and side effects of renal dysfunction and ototoxicity were investigated. The mean gestational age was 30.4 ± 5 weeks and mean body weight (Bw) was 1280.2 ± 809.8 g. The mean AMK dose was 14.1 ± 2.6 mg/kg and mean administration period was 10.1 ± 4.1 days. Blood concentration was measured 6.3 ± 2.3 days after AMK administration; mean peak and trough concentrations were 29.1 ± 7.5 μg/mL and 7.6 ± 6.9 μg/mL, respectively. Additionally, therapeutic effect was observed in all patients, and no significant change in serum creatinine (CRE) concentration (a marker of renal dysfunction) was observed, suggesting no renal dysfunction. Ototoxicity was observed in 4 patients, 3 of whom had trough concentrations ≥10 μg/mL. When we categorized patients into two groups using a trough cut-off value of 10 μg/mL, no difference in AMK dose was observed. However, there were significant differences in peak concentration, Bw, volume of distribution and CRE. Our findings suggest AMK trough concentration ≥10 μg/mL significantly affects ototoxicity in neonates.